RARE AND AGGRESSIVE METASTATIC PHEOCHROMOCYTOMA RECURRENCE IN A YOUNG ADULT MALE WITH MEN 2A SYNDROME - Hernandez, Edrome (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Multiple Endocrine Neoplasia 2A (MEN 2A) is characterized by 70-100% risk of medullary thyroid cancer, 50% risk of pheochromocytoma, and 20-30% risk of primary hyperparathyroidism mainly caused by RET mutation. Pheochromocytoma in MEN 2A is almost always benign and often follows an indolent course. CASE We demonstrate the clinical course and challenges in the management of a case of metastatic pheochromocytoma recurrence in a patient with MEN 2A. We present a 31-year-old male with histopathologically- confirmed bilateral pheochromocytoma occurring meta- chronously. He was subjected to left adrenalectomy and right adrenalectomy in 2014 and 2020, respectively. The patient was also diagnosed with primary hyperparathyroidism and medullary thyroid carcinoma presenting with mild hypercalcemia and multiple thyroid nodules. He underwent total thyroidectomy with neck dissection and left inferior parathyroidectomy. Genetic testing revealed the presence of a RET mutation. One year post-surgery, the patient had persistent elevation of 24-hour urine metanephrines [13.977 mg (NV: 0-1)]. Adrenal CT demonstrated a 2.1 cm ovoid focus in the right suprarenal region and I-131 MIBG scan showed avid uptake on the right frontal bone. Patient underwent excision of right adrenal bed and right frontal bone tumor which were confirmed to be metastatic pheochromocytoma on histopathologic report. He achieved normalization of 24-hour urine metanephrines 0.8 mg (0-1 mg) one month postoperatively. CONCLUSION Metastatic pheochromocytoma is only seen in less than 4% of MEN 2A. Metastatic PHEO recurrence has been reported only in few case reports and optimal management of these cases requires a multi-specialty approach.